10 little rubber ducks - Carle, Eric. ([New York] : HarperCollins, 2005)
When a storm strikes a cargo ship, ten rubber ducks are tossed overboard and swept off in ten different directions. The rubber duck's squeak is reproduced at the end of the book. Based on a factual incident.
Publisher's Weekly
School Library Journal starred
Wilson's Children
3.7
K-3
K-3
Keywords: Ducks -- Juvenile fiction; Sound effects books -- Specimens; Toy and movable books -- Specimens; Toys -- Juvenile fiction; Ducks -- Fiction; Sound effects books; Toy and movable books; Toys -- Fiction; Ducks -- Fiction; Toy and movable books; Toys -- Fiction